The Problem of Evaluation in the Rhetorical Criticism - Cosmin-Constantin BĂIAȘ (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
The field of the communication sciences is a hybrid field with various influences that can be observed in the research methods that are used: the quantitative-scientific and qualitative-interpretive methods. Rhetorical criticism as a qualitative research in the field of communication calls for its own evaluation standards. Our aim is to clarify, through a meta-analysis, the evaluation criteria proposed by different authors and the standards, after which an essay of the rhetorical criticism can be appreciated. We claim that a work of the rhetorical criticism is not just an exercise of creativity and originality, but rather a way of persuasive argumentation.